Synergistic Effects of Anti-CmeA and Anti-CmeB Peptide Nucleic Acids on Sensitizing Campylobacter jejuni to Antibiotics - Mu, Yang (American Society for Microbiology, 2013)
The CmeABC efflux pump in Campylobacter jejuni confers resistance to structurally divergent antimicrobials, and inhibition of CmeABC represents a promising strategy to control antibiotic-resistant Campylobacter. Antisense peptide nucleic acids (PNAs) targeting the three components of CmeABC were evaluated for inhibition of CmeABC expression. The result revealed a synergistic effect of the PNAs targeting CmeA and CmeB on sensitizing C. jejuni to antibiotics. This finding further demonstrates the feasibility of using PNAs to potentiate antibiotics against antibiotic-resistant Campylobacter.